The Lady as saint : a collection of French hagiographic romances of the thirteenth century - Cazelles, Brigitte (Middle Ages series., 1991)
Among the thirteenth-century saints exalted are female martyrs and hermits of early Christianity. In The Lady as Saint, Brigitte Cazelles offers the first English translation of these lives and provides extensive commentary on the portrayal of female spirituality.